2023
DOI: 10.1111/arcm.12855
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of archaeological lime mortars in a Ming dynasty tomb: A multi‐analytical approach

Abstract: Lime mortars have played an important role in constructing ancient Chinese masonry structures, including city walls, buildings, and tombs. A tomb built with lime mortars and stones belonging a Ming high-ranking official, Xu Jie, was discovered in Huzhou City of China. Eight different samples from Xu Jie's tomb, representing four types of lime-mortar-based materials: joint mortar between stone bricks, bedding mortar, grouting mortar, and plaster mortars were collected for analysis and comparison. The characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Due to the presence of organic matter, Gels 2024, 10, 191 2 of 17 the shortcomings regarding the water resistance and strength of lime mortars are effectively improved. The many advantages of organic-inorganic composite mortars have led to their widespread use in various applications, including indoor murals [5,6], tomb chamber murals [7], and wooden ships [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of organic matter, Gels 2024, 10, 191 2 of 17 the shortcomings regarding the water resistance and strength of lime mortars are effectively improved. The many advantages of organic-inorganic composite mortars have led to their widespread use in various applications, including indoor murals [5,6], tomb chamber murals [7], and wooden ships [8].…”
Section: Introductionmentioning
confidence: 99%
“…The earliest organic–inorganic composite building mortar was discovered in China and dates to 2300 BCE [ 9 ]. It has been shown that ancient traditional lime-based binders contained organic additives such as glutinous rice [ 10 , 11 , 12 , 13 ], tung oil [ 7 , 14 , 15 ], blood [ 16 , 17 , 18 , 19 ], egg white [ 20 , 21 ], sugar [ 20 ], gelatin [ 6 , 9 ], and peach gum [ 2 ]. Similarly, these lime-based mortars also emerged in other countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…They are easily soluble in water. Organisms such as bacteria and fungi can also produce water-insoluble biogenic calcium oxalates which were identified in historic lime mortars [53], [54] and other works of arts [55].…”
Section: Aging and Degradation Of Mortarsmentioning
confidence: 99%